PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA BOOKLET TERHADAP PENGETAHUAN IBU HAMIL YANG MENGALAMI HIPERTENSI DALAM KEHAMILAN (HDK) - isnaeni, Ely; Nur Pratiwi, Wahyu; Septina Margareta, Sheylla; Sujatmiko; Sriastutik, Wahyu (Universitas Kadiri, 2024)
Background : The factor that makes the high incidence of hypertension in pregnancy is the lack of knowledge of pregnant women. The increase in cases of hypertension in pregnancy, health education with booklet media plays an important role in increasing the insight of pregnant women's knowledge. Objective : Knowing the influence of health education with booklet media on knowledge of pregnant women who experience hypertension in pregnancy at Aura Syifa Kediri Hospital. Method : The research is a quantitative with a pretest-posttest research design. Sampling with non probability namely total sampling, obtained a sample of 30 respondents. Data collection using observation sheets, namely questionnaires. Results : There is an influence of health education with booklet media on the knowledge of pregnant women who experience hypertension in pregnancy at Aura Syifa Kediri Hospital. Suggestion : Researchers can further develop media used for health education counseling to be more varied to increase knowledge of pregnant women who experience hypertension in pregnancy. Keywords: Health Education, Hypertension, Knowledge, Pregnant Women